Whole blood‐based measurement of SARS‐CoV‐2‐specific T cells reveals asymptomatic infection and vaccine immunogenicity in healthy subjects and patients with solid‐organ cancers. Issue 2 (6th December 2021) - Scurr, Martin J.; Zelek, Wioleta M.; Lippiatt, George; Somerville, Michelle; Burnell, Stephanie E. A.; Capitani, Lorenzo; Davies, Kate; Lawton, Helen; Tozer, Thomas; Rees, Tara; Roberts, Kerry; Evans, Mererid; et al.
Abstract: Accurate assessment of SARS‐CoV‐2 immunity is critical in evaluating vaccine efficacy and devising public health policies. Whilst the exact nature of effective immunity remains incompletely defined, SARS‐CoV‐2‐specific T‐cell responses are a critical feature that will likely form a key correlate of protection against COVID‐19. Here, we developed and optimized a high‐throughput whole blood‐based assay to determine the T‐cell response associated with prior SARS‐CoV‐2 infection and/or vaccination amongst 231 healthy donors and 68 cancer patients. Following overnight in vitro stimulation with SARS‐CoV‐2‐specific peptides, blood plasma samples were analysed for TH 1‐type cytokines. Highly significant differential IFN‐γ + /IL‐2 + SARS‐CoV‐2‐specific T‐cell responses were seen amongst previously infected COVID‐19‐positive healthy donors in comparison with unknown / naïve individuals ( p  < 0·0001). IFN‐γ production was more effective at identifying asymptomatic donors, demonstrating higher sensitivity (96·0% vs. 83·3%) but lower specificity (84·4% vs. 92·5%) than measurement of IL‐2. A single COVID‐19 vaccine dose induced IFN‐γ and/or IL‐2 SARS‐CoV‐2‐specific T‐cell responses in 116 of 128 (90·6%) healthy donors, reducing significantly to 27 of 56 (48·2%) when measured in cancer patients ( p  < 0·0001). A second dose was sufficient to boost T‐cell responses in the majority (90·6%) of cancer patients, albeit IFN‐γ + responses were still significantly lower overall than those induced in healthy donors ( p  = 0·034). Three‐month post‐vaccination T‐cell responses also declined at a faster rate in cancer patients. Overall, this cost‐effective standardizable test ensures accurate and comparable assessments of SARS‐CoV‐2‐specific T‐cell responses amenable to widespread population immunity testing, and identifies individuals at greater need of booster vaccinations. Abstract : SARS‐CoV‐2 pandemic continues to cause morbidity and mortality especially in vulnerable patients. Monitoring individuals T and B cell responses to the virus is desirable in high risk populations after infection and/or vaccination. This paper describes a straightforward approach on a small whole blood sample to measure these responses.